Large Scale Identification of Genes Involved in Plant-Fungal Interactions Using Illumina's Sequencing-by-Synthesis Technology - Venu, R.C.; Zhang, Y.; Weaver, B.; Carswell, P.; Mitchell, T.K.; Meyers, B.C.; Boehm, M.J.; Boehm, M.J.
Deep transcriptome profiling of pathogen-infected tissues enhances the understanding of molecular mechanisms underlying host-pathogen interactions. Illumina's next generation sequencing technology sequencing-by-synthesis (SBS)is a powerful tool to rapidly sequence genomes and transcriptomes at an affordable rate. We modified the procedure for SBS library construction to significantly increase the efficiency of library construction. Using our improved method, two Sclerotinia homoeocarpa libraries were constructed from mycelia grown in potato dextrose broth (PDB)or potato dextrose agar (PDA)for 96 h, respectively, and two creeping bentgrass libraries were constructed from leaves 96 h after inoculation with S. homoeocarpa or water sprayed, respectively. About 4-7 million mRNA signatures were sequenced from each library. Sequence analysis using BLAST was performed against sequenced fungal genomes and rice genomic sequence to identify the expressed genes in both S.omoeocarpa mycelia and creeping bentgrass. Bioinformatic analysis identified many expressed genes in the pathogen and host. A public database to access the sequence data was developed at http://www.dstidb.org. Our results demonstrate how SBS technology can unravel transcriptome complexity during the creeping bentgrass- S. homoeocarpa interaction.
Keywords: SEQUENCING-BY-SYNTHESIS; TRANSCRIPTOME ANALYSIS; CREEPING BENTGRASS; SCLEROTINIA HOMOEOCARPA; BIOINFORMATICS